Journaling: Membentuk Efikasi Diri Klien X di Puskesmas Depok I, Sleman - Nikmah, Faiqotul Izzatin; Nurjannah; Suryadi (UIN Kiai Haji Achmad Siddiq Jember, 2024)
Students who are completing their thesis often experience various obstacles. The thesis remains a trigger for stress which can cause anxiety, depression, difficulty sleeping, decreased academic performance, use of illegal drugs, lack of self-confidence, risk of developing mental disorders, hopelessness, which increases the possibility of thinking to commit suicide. This research aims to see how clinical psychology shapes the self-efficacy of students who experience obstacles in writing their thesis using journaling techniques. This research uses a descriptive qualitative approach. The research method is based on descriptive data processing. Using this relaxation technique can help overcome the anxiety experienced by students. Apart from that, strategies to help clients face these obstacles include using journaling techniques or writing a journal to strengthen self-efficacy. Because one way to balance heavy loads and maximum results is to cultivate confidence in one's abilities.